A bayesian look at consumption - Honohan, P (Economic & Social Studies, 1982)
Precis: This paper assesses various possible explanations for savings behaviour in Ireland during the 1960s and 1970s. Attempts to discriminate between these rival hypotheses have been hampered by multicollinearity. This problem is tackled here by the addition of prior information along Bayesian lines, using the "contract curve" framework recently suggested by Leamer.
Keywords: Economics; Sociology